Thermal Modelling of Friction Stir Welding (FSW) Using Calculated Youngâs Modulus Values - Meyghani, B. (2019)
The temperature fluctuations present in Friction Stir Welding (FSW), require, detailed thermal analysis of the process. To achieve highly accurate results for the analysis, reliable material data should be obtained. Nevertheless, the material data that are presented in the literature are usually limited to lower strain rate regimes and lower temperatures. Thus, calculating the temperature dependent material properties helps improve the accuracy of the stimulated model. To achieve a reliable material data in the higher range of temperatures, this paper presents a mathematical formulation for calculating temperature dependent Youngâs modulus values. MATLABÂ® and ABAQUSÂ® software are employed for solving the governing equations and modelling the process, respectively. To compare the results and find the error percentage, the calculated and the documented (constant) values of Youngâs modulus are applied into two distinct finite element models. Finally, the developed model is validated by comparing the results obtained from experiments with published results. Â© 2019, Springer Nature Singapore Pte Ltd.